Thematization of Power in D. H. Lawrence’s Women in Love with reference to Nietzsche’s - The Will to Power - Ameen, Hishryar Muhammed; Ahmed, Khorsheed Mohammed Rasheed (European Scientific Journal, ESJ, 2016)
This paper gives a brief discussion on Nietzsche’s - The Will to Power. It aims to thoroughly discuss how this theme has been reflected within the plot and characters of D. H. Lawrence novel Women in Love. This paper briefly talks about Nietzsche and his concept of The Will to Power, Nietzsche’s influence over Lawrence, the relationships between characters in Women in Love and their significances, and The Will to Power and conflicts for dominations. Subsequently, it focuses on the Will to Power between male and female. Also, it considers social status as a source of power and authority. Finally, this study concludes on the type of Will to Power that is mainly reflected in Women in Love.